Mechanism of spontaneous initiation of ventricular fibrillation in patients with implantable defibrillators. - Xie, Eric; Mayer, Katarina; Capps, Melissa F.; Barth, Andreas S.; Love, Charles J.; Coronel, Ruben; Ashikaga, Hiroshi (Journal of Cardiovascular Electrophysiology, 2020)
Introduction: To improve the mechanistic understanding of spontaneous initiation of ventricular fibrillation (VF), we characterized the patterns of premature ventricular complex (PVC) preceding spontaneous VF in primary and secondary implantable cardioverter‐defibrillator (ICD) recipients. Methods and Results: A single‐center, cross‐sectional analysis of 1209 patients with primary and secondary prevention ICD identified 190 patients who received ICD therapy (firing or antitachycardia pacing) for VF or monomorphic ventricular tachycardia (MMVT). Initiation was quantified by the coupling interval (CI), the cycle length immediately preceding the CI (CL(−1)), the CI corrected by CL(−1) using Fridericia's formula (CIc), and the prematurity index (PI). In both VF (n = 44; 23%) and MMVT (n = 134; 71%), the most common pattern of initiation was late‐coupled PVC, followed by the short‐long‐short pattern. The parameters such as pre‐initiation median CL, CL(−1), CI, and PI were not significantly different between VF and MMVT for any patterns. At least some events (45% of VF and 63% of MMVT) had extremely long CIs beyond the QTc cut‐off estimated from the CL(−1), suggestive of initiation by a train of multiple PVCs or nonsustained VT instead of a single PVC. Conclusion: Some spontaneous VF events in ICD recipients appear to be initiated by a train of multiple PVC or nonsustained VT rather than a single PVC. This finding indicates that patterns of a single PVC are not an important determinant of VF initiation and thus account for conflicting results in previous studies.